Differences in infant feeding practices between Chinese-born and Australian-born mothers living in Australia: a cross-sectional study - Bolton, Kristy A. (BMC Pediatr, 2018)
BACKGROUND: Chinese immigrants are the third largest immigrant group in Australia. Recent qualitative evidence from Victorian Maternal and Child Health nurses indicate that infants of Chinese parents commonly have rapid growth trajectories and that high value is placed on rapid growth and having a fatter child; with low breastfeeding rates and overfeeding of infant formula. The aim of this study was to compare infant feeding practices (breastfeeding, infant formula, other liquids, solids) of Chinese-born and Australian-born mothers living in Australia. METHODS: Using the Australian National Infant Feeding Survey dataset (2010–2011), infant feeding data from Chinese-born mothers (n = 602) were compared with a random sub-sample of Australian-born mothers (n = 602). Group differences on feeding practices were tested using Chi-square or t-tests and the effect of ethnicity on infant feeding behaviours assessed using regression. RESULTS: Compared to infants of Australian-born mothers, infants of Chinese-born mothers were younger when they first consumed infant formula, water-based drinks and fruit juice and older when they first ate solid foods (p < 0.05). Furthermore, infants of Chinese-born mothers were less likely to have ever had cow’s milk (OR: 0.37 95%CI:, 0.18–0.78) and solids (0.41, 0.25–0.68); but were more likely to have ever had infant formula (2.19, 1.32–3.62), water (2.45, 1.55–3.87), toddler milk (3.39, 1.60–7.18), water-based drinks (e.g. cordial, soft drink, tea; 2.48, 1.12–5.49), and fruit juice (4.03, 2.50–6.51). Those ≤4 months of age were more likely to have had water-based drinks (7.77, 1.96–30.77) and fruit juice (3.44, 1.14–10.38) (p < 0.05) compared to infants of Australian-born mothers. CONCLUSION: Differences in mothers’ early infant feeding practices exist between Chinese-born and Australian-born mothers living in Australia. Better understanding these ethnically patterned infant feeding practices is important for identifying key opportunities to promote best nutrition and growth in early life in different ethnic groups within our population.